Manajemen Ekstrakurikuler Pendidikan Lingkungan Hidup Generasi Sadar Iklim di Sekolah Menengah Pertama Negeri 1 Panti - Nafirotul Hasanah; Nur Ittihadatul Ummah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The climate crisis and rapid social changes demand the education sector to produce a generation that is environmentally conscious and responsible. The Environmental Education Extracurricular Program